Population pharmacokinetics of remifentanil in critically ill patients receiving extracorporeal membrane oxygenation. Issue 1 (December 2017) - Yang, Seungwon; Noh, Hayeon; Hahn, Jongsung; Jin, Byung; Min, Kyoung; Bae, Soo; Kim, Jiseon; Park, Min; Hong, Taegon; Wi, Jin; Chang, Min
Abstract Extracorporeal membrane oxygenation (ECMO) is associated with pharmacokinetic (PK) changes of drugs. It presents considerable challenges to providing optimal dosing regimens for patients receiving ECMO. We aimed to describe the population PK of remifentanil in critically ill adult patients receiving venoartrial extracorporeal membrane oxygenation (VA-ECMO) and to identify determinants associated with altered remifentanil concentrations. The population PK model of remifentanil was developed using nonlinear mixed effects modelling (NONMEM). Fifteen adult patients who received a continuous infusion of remifentanil during VA-ECMO participated in the study. The PK of remifentanil was best described by a one-compartment model with additive and proportional residual errors. Remifentanil concentrations were affected by sex and ECMO pump speed. The final PK model included the effect of sex and ECMO pump speed on clearance is developed as followed: clearance (L/h) = 366 × 0.502sex × (ECMO pump speed/2350)2.04 and volume (L) = 41. Remifentanil volume and clearance were increased in adult patients on VA-ECMO compared with previously reported patients not on ECMO. We suggest that clinicians should consider an increased remifentanil dosing to achieve the desired level of sedation and provide a dosing regimen according to sex and ECMO pump speed.